Penggunaan Sari Buah Kelubi dan Gelatin Dalam Pembuatan Permen Jelly - Erika Meiliana Sari; Shanti Fitriani; Dewi Fortuna Ayu (Jurnal Teknologi dan Industri Pertanian Indonesia, 2022)
The acid content in kelubi can be used in the making of jelly candy with gelatin as a gelling agent. Jelly candy is a type of candy made from fruit extracts, sugar and gel forming material that looks clear, transparant and chewy. The purpose of this research was to get the best concentration of gelatin in the making of kelubi jelly candy based on Indonesian National Standard about jelly candy. This research was conducted experimentally by using a completely randomized design with four treatments and four replications. The treatment in this research was the concentration of gelatin (5%, 7.5%, 10% and 12.5%).  Data obtained were statistically analyzed using analysis of variance and continued with Duncan’s new multiple range test (DNMRT) at a 5% level. The result of this research showed that the concentration of gelatin significantly affected moisture, ash, reduction sugar, acidity (pH), total acid and sensory characteristics of color, taste and elasticity. The best treatment in this research was KG4 treatment (12.5% of gelatin) where moisture content of 19.10%, ash content of 0.83%, reduced sugar content of 14.21%, pH value of 4.15, and total acid of 2.99%.  The descriptive test showed that jelly candy had brownish yellow color, a little flavouring kelubi, sweet and sour taste, very chewy and overall assessment hedonically was favored by panelists.